Technostress sebagai Determinan Stres Kerja: Bukti Empiris Peran Dukungan Sosial di Industri Garmen - Galih Panjalu Pramono (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2026)
The rapid digital transformation in the manufacturing sector, particularly in the garment industry, has intensified employees’ reliance on information and communication technologies, which may generate new psychological pressures known as technostress. This study aims to examine the effect of technostress on work stress and to investigate the mediating role of social support in this relationship. Using a quantitative explanatory design, data were collected through a structured questionnaire administered to 139 employees of a garment manufacturing company producing for international brands in Semarang, Indonesia. The data were analyzed using multiple regression analysis and mediation testing. The results indicate that technostress has a positive and significant effect on work stress, while it negatively affects perceived social support. Furthermore, social support is found to have a significant negative effect on work stress and partially mediates the relationship between technostress and work stress. These findings suggest that technostress functions as a critical job demand that elevates employees’ psychological strain, whereas social support serves as a vital job resource that mitigates its adverse effects. The study contributes to the technostress and job demands–resources literature by providing empirical evidence from the manufacturing sector in a developing country context. Practically, the findings highlight the importance of strengthening social support mechanisms to reduce work stress in digitally intensive work environments.